The Yusuf trilogy. [part 3], Bal [videorecording (DVD)] - Kaplanoğlu, Semih, 1963-; Altas, Bora; Beşikçioğlu, Erdal; Özen, Tülin, 1979- (Olive Films, 2011)
Yusuf is an only child who lives with his parents in an isolated mountain area. The surrounding forest becomes a place of mystery and adventure when accompanying his beekeeper father on the job. The strong bond between father and son cannot protect the stuttering child from becoming an outsider during his first year of school. Yusuf's anxieties escalate when his father must travel to a faraway forest on a risky mission. With his father gone, Yusuf slips into silence to the distress of his mother.